Horticultural crop waste extracts as functional ingredients for enhanced surimi production - Vijay Kumar Reddy Surasani; Siddhnath Kumar; Arashdeep Singh; Isha Dudeja; Fatih Ozogul; Yesim Ozogul; Srinu Rathlavath; Lalitha Gnanasekaran; Saranya Vinayagam; Thanigaivel Sundaram; Maximilian Lackner; Pavan Kumar Dara (Applied Food Research)
Horticultural crop waste offers a valuable source of natural extracts rich in bioactive compounds, including polyphenols, which can be utilized to enhance the quality and sustainability of surimi production. Efficient utilization of these wastes would not only address environmental issues but also contribute to human health. Surimi is a fish mince-based product that is widely consumed in many parts of the world. Surimi is mainly produced from lean fish meat and is supplemented with external additives to control its quality during processing and storage. Horticulture waste is rich in phytochemicals. Many studies have demonstrated the application of extracts from horticultural crop waste in the surimi industry to improve its gel strength, color and functionality. Considering the recent advances in the utilization of natural extracts in surimi and potential applications of natural extracts from horticulture crop waste in the seafood industry, this article focuses on detailing recent developments in this field. This review summarizes the extraction and properties of natural extracts of horticultural crop waste and their effects on the quality of surimi. The natural extracts from horticultural crop waste can enhance the gel strength of surimi by interacting with the protein network, thereby preventing protein denaturation and improving the water-holding capacity. Moreover, natural extracts can also improve the color stability of surimi. Furthermore, natural extracts can also impart additional benefits, such as antimicrobial, antioxidant and anti-inflammatory activities, to surimi. Therefore, natural extracts from horticultural crop waste are promising candidates for the development of high-quality and functional surimi products. Therefore, natural extracts from horticultural crop waste are promising candidates for developing high-quality and functional surimi products. This review uniquely synthesizes findings across a broad spectrum of horticultural wastes, elucidates the specific biochemical interactions between plant-derived extracts and surimi proteins, and integrates the crucial, yet often overlooked, regulatory landscape, thus providing a holistic and practical guide for future innovation.